THE MENTAL HEALTH STATUS AND RELATED FACTORS AFFECTING THE MENTAL HEALTH OF UNIVERSITY STUDENTS DURING COVID-19 OUTBREAK - Tiaotrakul, Arphat; Thongngaen, Kanitin; Mahawan, Nonthawat; Boonkhan, Nitinan; Lathong, Piyachet; Kankaew, Siraphop; Jaruchart, Tussana (Journal of Education and Innovation, 2024)
The global crisis, COVID-19, induced disruption to routine instruction that impacted the academic life of higher education students. This study aimed to assess mental health status and study the factors affecting students’ mental health. The sample size was estimated using the Yamane formula (Yamane, 1973). Three hundred and sixty undergraduate students (ages 18-23 years) in the academic year 2022, were recruited using accidental sampling from the faculty of Education, Naresuan University. The Thai Mental Health Indicator (TMHI-15), with a value of validity (0.61) and reliability (0.83), was used to examine students’ mental health status. A set of mental health status-related factors questionnaire, with a value of validity (0.67-1.00) and reliability (0.90), was also used to survey factors involved in affecting students’ mental health status. Data were analyzed using multiple linear regression analysis. The findings revealed that 56.4% of students were in poor mental health status. Academic self-efficacy, adaptability, social support, and studying environment were significant predictors for students’ mental health with 22% (R2 = .22, Adjust R2 = .20, F = 5.98, p < .05). A factor that influenced students’ mental health the most was self-efficacy, while social support and adaptability were the second and third factors that influenced students’ mental health. These factors could play a mediating role related to student’s mental health status during the COVID-19 outbreak.